Dynamical origin of V-type asteroids outside the Vesta family - Roig, Fernando (2011)
We review some recent results on the long term dynamical evolution of V-type asteroids that point to their origin as fugitives from the Vesta family. Three scenarios are explored: (i) interplay of weak mean motion and non linear secular resonances in the inner Belt with the Yarkovsky effect, (ii) crossing of the 3:1 mean motion resonance with Jupiter, and (iii) evolution by planetary encounters and resonance stickiness. These mechanisms may explain a large fraction of the V-type asteroids that are observed outside the Vesta family, but there are some particular cases that would need other explanations.